Effective Classroom Experience via Social Media: An Experience in UNITEN - Nabil Ahmad Zawawi, Md.; ., . (International Journal of Engineering and Technology, 2018)
The impact of social media towards many industries mainly business and entertainment is very notable due to the availability of affordable smartphones to the masses. However, in contrast to that, this technology is not utilized extensively to extend the classroom experience for teaching and learning at a university level. While we have tools such as Moodle or other similar Learning Management System (LMS), it does not really provide the sense of presence that the social media tool is providing to its socially active new generation of learners. This paper identifies features in the social media tool (i.e, Facebook) and how it can be used to provide a better after class experience. These features are identified after implementation on different groups of students. The effectiveness is measured based on the studentsâ€™ grades, their participation level in the class and the lecturerâ€™s performance evaluation at the end of each semester. The paper also suggested proper guidelines for optimizing the use of social media as a tool to assist in teaching and managing classes with large group of students.Â